Analisis Pengaruh Beban Kerja Terhadap Keselamatan Kerja Pada Bagian Produksi PT. Petrokimia Dengan Menggunakan Metode NASA-TLX - Ahmad Syarifuddin Maulana; Naniek Ratni Juliardi A.R (MAMEN: Jurnal Manajemen, 2024)
PT Petrokimia as a leading fertilizer producer in Indonesia, bears great challenges in its operations. Production employees at the company face high pressure in performing their duties, which in turn increases their mental workload. In addition, the production employees at PT Petrokimia are also exposed to significant noise levels on a daily basis. The analysis showed that the intensity of noise exposure at PT Petrokimia reached 87.4 - 101.4 dBA, exceeding the Threshold Value (NAB) set by PERMENAKER No.5 Year 2018. Based on this, an in-depth analysis of the mental workload faced by employees and the factors that influence it is needed. Appropriate corrective measures can be identified after conducting this analysis. The method used to measure mental workload is the NASA TLX method. The results of the analysis on 42 employees showed that 6 employees experienced high mental workload, while 36 employees experienced very high mental workload. The most dominant factor causing mental workload is Noise at 46.9%.